Sifat Fisika dan Kimia, Indeks Iritasi dan Aktivitas Anti-inflamasi dari Salep Minyak Atsiri Syzygium aromaticum dengan Penambahan Enhancer - Alfian, Muhammad; Sugihartini, Nining; Yuliani, Sapto (JURNAL ILMU KEFARMASIAN INDONESIA, 2023)
This research aimed to evaluate how enhancers affect the properties of Syzygium aromaticum oil in both water-soluble and hydrocarbon bases. Physical and chemical characteristic tests, irritation index evaluations, and anti-inflammatory activity assessments were carried out to analyze the Syzygium aromaticum oil ointment. The pH tests were conducted to measure the chemical characteristics and viscosity, adhesivity, spreadability tests were conducted to measure the physical characteristics of the ointment. Rabbit-based tests were used to determine the irritation index, mice induced by crotton oil were used in anti-inflammatory activity assessments. The pH tests revealed no significant differences between both of ointments. The ointment in the water-soluble base had higher viscosity and adhesivity but lower spreadability than the ointment in the hydrocarbon base. The epidermis thickness of watersoluble and hydrocarbon-based ointments was 3.81±0.40 μm and 4.22±0.15 μm, while the number of cells with COX-2 expression was 18.24±6.51 and 21.01±5.96. The addition of enhancers did not cause any irritation in either ointment. The study concluded that the formula of Syzygium aromaticum oil in a water-soluble ointment with the addition of propylene glycol and oleic acid (70:30) as enhancers provided better physical and chemical characteristics, a lower irritation index, and higher anti-inflammatory activity compared to the hydrocarbon.